The Effect of Health Education on Mother's Knowledge Attitudes and Behavior in Giving Care to Low Birth Weight Babies - Pratiwi, Dian; Ismail, Djauhar; Mufdlilah, Mufdlilah; Cholsakhon, Panyada (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2021)
The number of low-birth-weight babies (LBW) who returned to the hospital after returning home had increased from 2015 to 2016. The results of the interview revealed that mothers who had LBW did not thoroughly understand providing care for LBW after returning from the hospital. This study aims to determine the effect of health education on a mother's knowledge, attitude and behaviour in providing care to LBW. This study is quasi-experimental with a pre-posttest approach non-equivalent to the control group, with 66 respondents fulfilling the inclusion criteria. The inclusion criteria in this study were post-partum mothers on the second day who had babies with a birth weight of 1500 grams-2499 grams and were willing to be respondents. The sampling technique was purposive sampling. The statistical test employed independent t-test, paired t-test, and chi-square. Knowledge scores before and after treatment were significantly different in the intervention group and control group, with a p-value in the intervention group 0.00, while the knowledge and attitude scores in the control group were 0.00 and the behavioural scores were 0.11. There was a significant difference in the increase in knowledge, attitudes and behaviour scores in both groups. The p-value of knowledge and attitudes is 0.00, and the p-value of behaviour is 0.01. Hence, there is an increase in mothers' knowledge, attitudes, and behaviour after being provided with health education using a booklet.